Insights from Local Community on Changing Availability of Non-Timber Forest Products under Climate Change in Panchadeval Binayak Municipality, Achham District, West Nepal - Shahi, Sabina; Paudel, Hem Raj; Ghimire, Shiba Raj (Journal of Plant Resources, 2022)
Local people in the hilly area depend upon different varieties of non-timber forest products (NTFPs) such as foods, medicines, spices, etc. for income generation, except timber. This paper highlights the perception of local people over current situation including status of availability of NTFPs under changing climate. Data were collected by using questionnaire survey and key informant interview (KII) in 9 wards of Panchadeval Binayak Municipality during April, 2022. Altogether 225 interviews were taken with the oldest family members of each household. Total 89 species of NTFPs were noted. Majority of species were used for medicinal purpose (53.92%), followed by edible (30.33%) whereas 15.73% species were used for fodder, fuelwood and other purposes. Climate change and availability of NTFPs were analyzed according to people’s perception. The study showed that about 96% of respondents agreed to increase in temperature, 84.83% believed in decrease of rainfall, whereas13.33% agreed the rainfall to be unpredictable. Due to those climatic changes, the availability of NTFPs is predicted to decrease and the dependency of people on NTFPs is in critical condition in this municipality. Therefore, it is urged to develop some climate change coping strategies at the local and national level which will assure the NTFPs availability for the local people.